2000
DOI: 10.1021/la990933c
|View full text |Cite
|
Sign up to set email alerts
|

Dispersed Structure and Rheology of Lipophilized-Smectite/Toluene Suspensions

Abstract: Dispersed rheology of lipophilized-smectite (SAN)/toluene (TOL) suspensions with various concentrations φ of (0.03-3.77) × 10 -2 vol fraction was examined by a stress-controlled rheometer and Ubbelohde type viscometer. Under the quiescent state of the SAN/TOL suspensions, the original laminate structure in the solid state of SAN was lost and exfoliation of the silicate layers took place as revealed by X-ray diffraction analysis. In the dilute SAN/TOL suspension with 10 2 φ e 0.2, the value of ηsp/φ (ηsp being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 6 publications
3
22
0
Order By: Relevance
“…In our previous study [21] on lyophilized smectic clay-toluene suspensions, we observed this type of shear thinning feature of the clay particles in the rapid shear flow. Such a feature is strongly dependent on the shear rate in the dynamic measurements, because of the formation of the shear-induced alignment of the dispersed clay particles.…”
Section: Dynamic Oscillatory Shear Measurementssupporting
confidence: 53%
“…In our previous study [21] on lyophilized smectic clay-toluene suspensions, we observed this type of shear thinning feature of the clay particles in the rapid shear flow. Such a feature is strongly dependent on the shear rate in the dynamic measurements, because of the formation of the shear-induced alignment of the dispersed clay particles.…”
Section: Dynamic Oscillatory Shear Measurementssupporting
confidence: 53%
“…
In a series of our studies on a synthetic smectic clay/organic monomer suspensions, 1) we have devoted to understanding of thixotropic behavior under shear flow. To understand this intriguing issue, we should follow directly an internal structural change of the suspensions under shear flow.
…”
mentioning
confidence: 99%
“…It has been reported that liophilized clay, such as Na-MMT intercalated with alkylammonium ions, can readily disperse into toluene. 16 In our system, we also obtained a slightly brown but nearly transparent suspension when organoclay was suspended in toluene. The following reports the chemical modification of the organoclay in toluene using trialkoxysilane.…”
Section: Modification Of Organoclaymentioning
confidence: 70%